2004
DOI: 10.1021/ef034098p
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization of Mixed Paraffin from Model Waxy Oils and the Influence of Micro-crystalline Poly(ethylene-butene) Random Copolymers

Abstract: We report rheological, microscopic, and calorimetric studies of the crystallization of long chain n-paraffins and their mixtures from model waxy oils and the effect of microcrystalline poly(ethylene-butene) (PEB) random copolymers. Optical micrographs and differential scanning calorimetry (DSC) reveal that the crystals formed from decane solutions of binary mixtures of C36 + C32 and of C32 + C28 are of mixed composition, whereas solutions of C28 + C24, C36 + C28, C32 + C24, and C36 + C24 form separate crystal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
97
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 69 publications
(101 citation statements)
references
References 26 publications
4
97
0
Order By: Relevance
“…Wax tends to crystallize into quite complex shape such as rod-like or shuttlelike structures under the interference of PEB. These structures can reduce the yield stress of waxy oils compared to the plate-like crystals formed in the absence of PEB (Guo et al 2004c(Guo et al , 2006Tinsley et al 2007a). In addition, they provided a kind of hydroxyl-grafted PEB polymer (PEB-OH), which seems more efficient in reducing the yield stress of asphaltene-contained crude oils than PEB which can be interpreted by the dispersion effect of the polar group (-OH) (Guo et al 2004a).…”
Section: Poly(ethylene-butene) (Peb)mentioning
confidence: 99%
See 1 more Smart Citation
“…Wax tends to crystallize into quite complex shape such as rod-like or shuttlelike structures under the interference of PEB. These structures can reduce the yield stress of waxy oils compared to the plate-like crystals formed in the absence of PEB (Guo et al 2004c(Guo et al , 2006Tinsley et al 2007a). In addition, they provided a kind of hydroxyl-grafted PEB polymer (PEB-OH), which seems more efficient in reducing the yield stress of asphaltene-contained crude oils than PEB which can be interpreted by the dispersion effect of the polar group (-OH) (Guo et al 2004a).…”
Section: Poly(ethylene-butene) (Peb)mentioning
confidence: 99%
“…This evaluation revealed that the efficiency of PEB 7.5 in controlling the crystallization of long wax molecule (C36) is relatively greater than that of short wax molecule (C24). However, for a certain wax molecule, Guo et al (2004c) claimed that PEB 10 which has an average 10 ethyl branches per 100 backbone carbon is more active in reducing the yield stress than PEB 7.5. These experimental results suggest that the overall performance of wax crystal modifiers is dependant not only on the wax structure but also on the structure of themselves (Ashbaugh et al 2005).…”
Section: Poly(ethylene-butene) (Peb)mentioning
confidence: 99%
“…With the increase of the concentration of MASCs from 0 to 100 ppm, the yield stress of the model waxy oil decreased significantly. However, further increase of the MASC concentration to 200 ppm results in the enhancement of the yield stress of model waxy oil due to the "bridge effect" of extra polymers [3]. Obviously, 100 ppm (0.10 wt-%) of MASCs is the best concentration for the reduction of yield stress of model waxy oil (Fig.…”
Section: Effect Of Mascs On the Model Oil And Crude Oilmentioning
confidence: 97%
“…The long chain paraffins and asphaltenes will precipitate and deposit at the pipe walls, reducing oil flow and even blocking the pipeline [1]. The problem becomes more serious for offshore deep-sea wells, where the temperature at the sea bed can be 4°C or lower [2,3]. To solve this problem, heating and mechanical pigging are always applied in the petroleum industry [4].…”
Section: Introductionmentioning
confidence: 99%
“…Guo et al (2004) found that the binary C n in decane solutions have a lower yield stress than the mono-disperse C n -decane solution. Senra et al (2008Senra et al ( , 2009 found that co-crystallization inhibits the formation of a gel by developing weaknesses in the crystal structure.…”
Section: Introductionmentioning
confidence: 98%